Weakly negative permittivity of MWCNT/TiN/CCTO ternary ceramics sintered in argon and nitrogen atmosphere. Issue 22 (15th November 2021) - Sun, Kai; Yang, Pengtao; He, Qifa; Tian, Jiahong; Duan, Wenxin; Wu, Xinfeng; Qu, Yunpeng; Du, Hailiang
Abstract: When seeking for satisfactory metacomposites with negative permittivity behavior, an important factor which should be taken into consideration is how to realize a weakly negative permittivity (less than 100). A novel strategy has been proposed accordingly to prepare ternary multiwalled carbon nanotubes/titanium nitride/copper calcium titanate (MWCNT/TiN/CCTO) composites by a facile sintering method in an inert atmosphere. The negative permittivity was observed after the TiN-MWCNT network was constructed among the composites. TiN provided sufficient free electrons and MWCNT were regarded as transporter bridge. Under the synergistic effect of TiN and MWCNT, the negative permittivity decreased by several orders of magnitude owing to the dilution of overall electron density in the resulting composites. Exceptionally, when the permittivity switched from positive to negative along with a resonance, a Lorentz-like negative permittivity was observed in low frequency region. Meanwhile, the Drude-like negative permittivity derived from plasma oscillation was also observed in the higher frequency region. Further investigation confirmed that the permittivity was closely related to the reactance. The positive-negative reactance transition was consistent with the negative-positive permittivity transition, and the epsilon-near-zero was achieved near the zero-crossing point of permittivity. Moreover, the influence of different sintering atmospheres (nitrogen and argon) on the negative permittivity behavior was also explored. This work provides an effective approach for the realization of weakly negative permittivity, and presents, to our knowledge, the first investigation into the influence of sintering atmosphere on negative permittivity.